ABC News/Washington Post Poll, September 1985 ([Verlag nicht ermittelbar], 1988)
In this survey respondents were asked a series of questions related to Reagan's performance as president, his relationship with Congress, South Africa, apartheid, and the trade deficit. Respondents' attitudes toward various health problems in the United States were also examined, with questions focusing on AIDS, cigarette smoking, and osteoporosis. Demographic characteristics also were recorded.